Marketing of Early Childhood Education Institution: Covid-19 Pandemic Vs. Normal - Abdul Latif, Muhammad; Munastiwi, Erni; Humaida, Rifqi (Universitas Nahdlatul Ulama Surabaya, 2021)
The new normal era resulted in many factors, including early childhood education institutions, such as the Primagama Kindergarten in Yogyakarta. The life and death of an institution lie in how the marketing of the educational institution is. This study aims to describe the marketing strategy, impact, and marketing barriers of Primagama Yogyakarta Kindergarten in the New Normal Era. This research uses the descriptive qualitative method. They were collecting data by observation, interviews, and documentation. The analysis uses the Milles and Huberman model. Test the validity of the data using triangulation of sources and techniques. This study indicates that the marketing of the Primagama Yogyakarta Kindergarten institution begins with building a brand with show ups, collaboration with TV stations, radio, mass media, and active social media. Furthermore, the marketing of Primagama Kindergarten begins with market research, determining various strategies such as Facebook, Instagram, Twitter, and website and controlling by collecting suggestions from various parties. The era of the marketing pandemic is carried out by maximizing social media. The marketing impact of the pandemic era is the lack of offline customers. This is because there are obstacles in the pandemic era, including the limitation of meeting face to face, the government's appeal for a ban on face-to-face contact, and the declining purchasing power of the people. The research findings contribute to marketing strategies for early childhood education institutions in the pandemic era that can use social media.